Effects of the pruning intensity and tree size on multi-stemmed Prosopis flexuosa trees in the Central Monte, Argentina - Alvarez, Juan Agustin (2013)
Forestry use in Prosopis flexuosa woodlands in the Central Monte is limited by low wood productivity and by most of the trees being multi-stemmed. Desert inhabitants have turned pruning into a common practice to get some forest products, increase wood production and improve tree shape. In this study we tested pruning practices used by locals on trees of different diameter classes and different pruning intensities in the aeolian plains of the Central Monte Desert. Two trials were conducted: (a) we tested the effects of pruning on three types of trees: adult multi-stemmed trees (7.5–15 cm basal diameter; n = 12 for pruned trees and 10 for control), young trees (3–7.5 cm basal diameter; n = 20 for pruned trees and 18 for control), and saplings (<3 cm basal diameter; n = 15 for pruned trees and 18 for control); (b) we compared the effects of different pruning intensities: heavy pruning (50% of crown removed and n = 10), intermediate pruning (25% of crown removed; n = 10), and unpruned individuals (n = 10). Basal diameters of all stems, total tree height, largest and smallest crown diameters were measured yearly. We estimated the equivalent basal diameter (EBD) and crown volume. Linear mixed models (LMM), in continuous variables, and general linear mixed models (GLMM), in discrete variables, were used for evaluating the effects of the treatments on the different variables. The response observed in pruned trees was an increased length of branches, which in both trials translated into increased crown diameter and volume. No initial response was recorded in basal diameter growth of the remaining stem. In adult trees, an increase in basal diameter was detected five years after pruning. A greater response of crown growth was found in individuals subjected to heavy pruning vs. individuals under intermediate pruning. Results suggested that pruning could improve the shape of Prosopis in the short run, and increase stem diameter growth in the long run, as observed for other tree species of Prosopis that received pruning throughout the world. This suggests that this practice could be potentially used to obtain poles and firewood without a decrease in wood productivity but with an increase in branch growth, and, in consequence, it could be included in silvicultural management of woodlands dominated by multi-stemmed trees and in models of sustainable management at local scale.